The study of polymer material characterisation using M-Z-N statistical analysis method - Muhamad Arif Fadli Ahmad,; Mohd Zaki Nuawi,; Nadia F. Mohamed,; Zaliha Wahid,; M. Dirhamsyah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper proposes an implementation of alternative statistical signal analysis method in characterising material properties of polymer using impulse excitation technique (IET) in accordance with ASTM E1876 standard. Five types of cylindrical shape polymer specimens are used, namely acrylics (AC), poly vinyl chloride (PVC), polyethylene (PE), cast nylon (MC), and polyoxymethylene (POM). Experimental procedure is done based on non-destructive testing (NDT) concept by tapping the specimens using an impact hammer within a specific range of impact force, while accelerometer sensor Endevco 751-100 is used to detect the vibration produced. The detected vibration and the impact force signal which is triggered by impact hammer are captured using NI 9234 data acquisition device and computer. The signal is interpreted and statistically analysed using Mesokurtosis Zonal Non-parametric (M-Z-N) analysis method. As a result, mathematical model equations for determining two material properties which are tensile strength and thermal conductivity have been successfully developed. They are derived through correlation between the signal data and M-Z-N coefficient. Verification of the equation is done and the calculated errors to be in the range of 5.55% to 9.74%. Hence, this proves that the correlation can be used as a standard for determining these material properties through M-Z-N method, which is efficient and low cost.